Stress-responsive pathways and small RNA changes distinguish variable developmental phenotypes caused by MSH1 loss. Issue 1 (December 2017) - Shao, Mon-Ray; Kumar Kenchanmane Raju, Sunil; Laurie, John; Sanchez, Robersy; Mackenzie, Sally
Abstract Background Proper regulation of nuclear-encoded, organelle-targeted genes is crucial for plastid and mitochondrial function. Among these genes, MutS Homolog 1 (MSH1 ) is notable for generating an assortment of mutant phenotypes with varying degrees of penetrance and pleiotropy. Stronger phenotypes have been connected to stress tolerance and epigenetic changes, and inArabidopsis T-DNA mutants, two generations of homozygosity with themsh1 insertion are required before severe phenotypes begin to emerge. These observations prompted us to examine howmsh1 mutants contrast according to generation and phenotype by profiling their respective transcriptomes and small RNA populations. Results Using RNA-seq, we analyze pathways that are associated withMSH1 loss, including abiotic stresses such as cold response, pathogen defense and immune response, salicylic acid, MAPK signaling, and circadian rhythm. Subtle redox and environment-responsive changes also begin in the first generation, in the absence of strong phenotypes. Using small RNA-seq we further identify miRNA changes, and uncover siRNA trends that indicate modifications at the chromatin organization level. In all cases, the magnitude of changes among protein-coding genes, transposable elements, and small RNAs increases according to generation and phenotypic severity. Conclusion Loss ofMSH1 is sufficient to cause large-scale regulatory changes in pathways that have been individually linked to one another, but rarely described all together within a single mutant background. This study enforces the recognition of organelles as critical integrators of both internal and external cues, and highlights the relationship between organelle and nuclear regulation in fundamental aspects of plant development and stress signaling. Our findings also encourage further investigation into potential connections between organelle state and genome regulation vis-á-vis small RNA feedback.